The Influence Of Location And Promotion On Product Purchasing Decisions (Survey on Consumers Cafe Jelang Hari Tasikmalaya) - Gilang Tendi Abdillah; Rita Tri Yusnita; Barin Barlian (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of location and promotion on purchasing decisions at Cafe Jelang Hari (Survey of Cafe Jelang Hari). The method used is a Quantitative approach with the Survey method. With a research sample of 100 consumers of Cafe Jelang Hari. The data used is using primary data. The analytical tool used in this research is multiple regression using SPSS 25.0. The results showed that the location perceived by consumers of Cafe Jelang Hari has very good criteria. Promotion on Cafe Jelang Hari products has very good criteria. Purchasing decisions at Ahead of Day Cafe consumers have very good criteria. Simultaneously, location and promotion have a significant influence on purchasing decisions. Partially, location has a significant influence on purchasing decisions. Partially Promotion has a significant effect on purchasing decisions.